Self-service applications using IBM WebSphere v5.0 and WebSphere MQ Integrator v2.1 : patterns for e-business series - Kovari, Peter (IBM redbooks., 2003)
This IBM Redbooks publication introduces the Router and Decomposition application patterns for Self-Service e-business applications. The book discusses the messaging and transactional capabilities of an application. This book is a valuable source for IT architects, IT specialists, application designers, application developers, system administrators, and consultants. Part 1, Patterns for e-business, introduces the Patterns for e-business concept, focusing particularly on the Self-Service business pattern and the Router and Decomposition application patterns. Part 2, Guidelines, provides guidelines for messaging and transactional applications, including application design and development and some of the non-functional requirements for such applications, including security and system management and performance. In the Appendix, you will find details on how to set up and configure both the development and runtime environments for the sample application discussed in this book. Please note that the additional material referenced in the text is not available from IBM.